CONVERGENCE AND DIVERGENCE DURING THE ADAPTATION TO SIMILAR ENVIRONMENTS BY AN AUSTRALIAN GROUNDSEL. (22nd May 2013) - Roda, Federico; Liu, Huanle; Wilkinson, Melanie J.; Walter, Gregory M.; James, Maddie E.; Bernal, Diana M.; Melo, Maria C.; Lowe, Andrew; Rieseberg, Loren H.; Prentis, Peter; Ortiz‐Barrientos, Daniel
<x xml:space="preserve">Abstract</x> Adaptation to replicate environments is often achieved through similar phenotypic solutions. Whether selection also produces convergent genomic changes in these situations remains largely unknown. The variable groundsel, Senecio lautus, is an excellent system to investigate the genetic underpinnings of convergent evolution, because morphologically similar forms of these plants have adapted to the same environments along the coast of Australia. We compared range‐wide patterns of genomic divergence in natural populations of this plant and searched for regions putatively affected by natural selection. Our results indicate that environmental adaptation followed complex genetic trajectories, affecting multiple loci, implying both the parallel recruitment of the same alleles and the divergence of completely different genomic regions across geography. An analysis of the biological functions of candidate genes suggests that adaptation to coastal environments may have occurred through the recruitment of different genes participating in similar processes. The relatively low genetic convergence that characterizes the parallel evolution of S. lautus forms suggests that evolution is more constrained at higher levels of biological organization.